2022
DOI: 10.4314/bcse.v35i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Novel 6-aryl-7-alkyl/aryl-[1,2,4]triazolo[4,3-a][1,3,5]triazine-5(6H)-thiones, processes for their preparation, characterization and evaluation of their in vitro antioxidant activity

Abstract: ABSTRACT. A series of nine new 6-aryl-7-alkyl/aryl-[1,2,4]triazolo[4,3-a][1,3,5]triazine-5(6H)-thiones (2a-i) were synthesized by a reaction of N-triazol-3-yl imidates (1) with three different isothiocyanate derivatives (RNCS)  in refluxing toluene. The structures of the final heterocyclic compounds were confirmed by 1H-NMR, 13C-NMR, FT-IR, elemental analysis, and mass spectral analysis. The target compounds (2a-i) were in vitro screened for their activity as antioxidants using DPPH (2,2′-diphenyl-1-picrylhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…FRAP assay of SWE extracts was performed using the method described by Hajri et al 23 . The reagent was formed of 300 mM acetate buffer (3.1 g of C 2 H 3 NaO 2 ·3H 2 O and 16 mL of C 2 H 4 O 2 ), 10 mM trypyridyltriazine (TPTZ) solution (3.1233 g TPTZ in 40 mM HCl), and 20 mM FeCl 3 ·6H 2 O solution.…”
Section: Methodsmentioning
confidence: 99%
“…FRAP assay of SWE extracts was performed using the method described by Hajri et al 23 . The reagent was formed of 300 mM acetate buffer (3.1 g of C 2 H 3 NaO 2 ·3H 2 O and 16 mL of C 2 H 4 O 2 ), 10 mM trypyridyltriazine (TPTZ) solution (3.1233 g TPTZ in 40 mM HCl), and 20 mM FeCl 3 ·6H 2 O solution.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds ( 78 ) are the molecular hybrids of s -triazine and 1,3,5-triazine which are fused with each other giving rise to novel pharmacophores. 92 These bioconjugates were synthesized in good yield via the conventional method and their biological activity was examined as DPPH free-radical scavenger, that is to say, antioxidant. After complete examination and evaluation, and through SAR analysis it was confirmed that compounds possessing hydroxyl group in their structures depicted more efficiency as a free radical scavenger in in vitro analysis than other compounds in the same series due to electron-donating effect.…”
Section: Biological Activities Of S-triazine-based Heterocyclic Hybridsmentioning
confidence: 99%